The Influence of Recruitment Strategy, Employee Morale, and Compensation Packages on Talent Acquisition in Technology Companies in Indonesia - Hidayati, Nanda; Subroto, Setyowati; Anani, Siske; Djou, Sitti Husna Noviana; Musa, Maman (The Eastasouth Management and Business, 2024)
This study examines the effect of recruitment strategy, employee morale, and compensation package on talent acquisition in technology companies in Indonesia through a quantitative analysis. Data were collected from 150 employees using a structured questionnaire, and analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate significant positive relationships between recruitment strategy, employee morale, compensation package, and talent acquisition. Effective recruitment strategies, positive employee morale, and competitive compensation packages are crucial for attracting and retaining top talent in the technology sector. The findings provide practical implications for organizations to optimize talent acquisition practices and enhance organizational performance in the digital age.